2019
DOI: 10.1186/s12889-019-7010-z
|View full text |Cite
|
Sign up to set email alerts
|

Dementia awareness and risk perception in middle-aged and older individuals: baseline results of the MijnBreincoach survey on the association between lifestyle and brain health

Abstract: Background The total number of people with dementia is increasing worldwide, due to our aging society. Without a disease-modifying drug available, risk reduction strategies are to date the only promising way to reduce dementia incidence in the future. Substantial evidence exists that lifestyle factors contribute to the risk of dementia, such as physical exercise, mental activity and (non-)smoking. Still, most people seem unaware of a relationship between lifestyle and brain health. This paper inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
87
3
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 29 publications
15
87
3
11
Order By: Relevance
“…A few studies conducted in China focused mainly on the recognition of prodromal symptoms of dementia [18,24]. The present results suggested that the overall understanding of factors associated with dementia among the Chinese population was more comprehensive than we initially believed based on similar studies in other countries [19,29,30]. This finding might have two explanations.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…A few studies conducted in China focused mainly on the recognition of prodromal symptoms of dementia [18,24]. The present results suggested that the overall understanding of factors associated with dementia among the Chinese population was more comprehensive than we initially believed based on similar studies in other countries [19,29,30]. This finding might have two explanations.…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies indicated that several reasons, including concerns about the side effects, high financial burden and inadequate health literacy, might lead to poor medication adherence [34,35]. Other studies also found that people had less knowledge about the role of cardiovascular disease management in the development of dementia [19,36]. Thus, medical factors associated with the risk reduction of dementia need to be popularized in the general public.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies that were conducted in China mainly focused on the recognition of prodromal symptoms of dementia [20,26]. The present results suggest that the overall understanding of factors that are associated with dementia among the Chinese population is more comprehensive than we initially believed based on similar studies in other countries [21,28,29]. This finding may have two explanations.…”
Section: Discussionsupporting
confidence: 48%
“…Moreover, medication refusal is common in the general population [33], and people are often more concerned about the side effects of antihypertensive and hypolipidemic drugs than their beneficial effects [34]. Other studies also found that people had less knowledge about the role of cardiovascular disease management in the development of dementia [21,35]. Thus, medical factors that are associated with the prevention of dementia need to be popularized in the general public.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation